Timing of Ethylene Inhibition Affects Internal Browning and Quality of ‘Gala’ Apples in Long-Term Low Oxygen Storage - DeEll, Jennifer R.; Lum, Geoffrey B.; Mostofi, Younes; Lesage, Sky K. (Frontiers in Plant Science, 2022)
The objective of this study was to evaluate the timing of ethylene inhibition with preharvest and postharvest 1-methylcyclopropene (1-MCP) treatments on internal browning and quality of ‘Gala’ apples in long-term low O2 storage. Preharvest 1-MCP orchard spray was applied to ‘Gala’ apples at the label rate, while postharvest 1-MCP (1 µL L-1) treatments were made at 0.5°C either at harvest time or after storage. Apples were stored in 1.5 kPa O2 + 0.5 kPa CO2 or 0.6 kPa O2 + <0.5 kPa CO2 for 9 months in the first year and 1.5, 1.0, or 0.5 kPa O2 + 0.5 kPa CO2 for 8 months in the second year. Internal browning developed in both years of study and apples stored in 0.5-0.6 kPa O2 had significantly less than those in higher O2. The effect of 1-MCP on internal browning was negligible in 0.5-0.6 kPa O2 storage. ‘Gala’ stored in 1.5 kPa O2 and treated with 1-MCP after storage had significantly less internal browning with preharvest 1-MCP than those without preharvest treatment. Apples treated with 1-MCP at harvest time, instead of after storage, did not exhibit this effect. Preharvest 1-MCP-treated fruit maintained greater firmness than those without preharvest 1-MCP, and this effect was further enhanced when 1-MCP was applied after storage. Postharvest 1-MCP had no effect on firmness retention in fruit without preharvest 1-MCP, but lower O2 maintained greater firmness. Preharvest 1 MCP had no significant effect on internal ethylene, whereas it was reduced by 1-MCP at harvest time in the first year of study and affected only by storage regime in the second year, with lower concentration in fruit from 0.5 kPa O2 than in higher O2. Postharvest 1-MCP consistently reduced greasiness, regardless of treatment timing and storage regime. There was no greasiness in apples treated with 1-MCP at harvest and then held in 0.5 kPa O2. Overall, storage regimes with less than 1 kPa O2 provided the least amount of internal browning and best quality attributes. Ethylene inhibition provided further benefits, but this was dependent on the timing of 1-MCP treatment.